Analisis Ekonomi Usaha Minyak Kelapa Murni (Virgin Coconut Oil) di Rumah Produksi KenaKetik Nita - Maria Sharlina Yesi; Sarlina Noni (Peneliti.net, 2022)
Virgin Coconut Oil (VCO) is a modern product of coconut fruit that has the ability to improve health, treat, and even be used in the field of cosmetics. This research aims to find out the income and feasibility of pure coconut oil business in the production house Kena Ketik Nita. Use cost, revenue, acceptance and business feasibility analysis to answer research problems. As for the results of research obtained that the business of pure coconut oil production in the production house KenaKetik Nita suffered a loss of - 206,981,750 in one production. As for the results of research obtained that the business of pure coconut oil production in the production house KenaKetik Nita suffered a loss of - 206,981,750 in one production.